Sosialisasi Dampak Penggunaan Handphone pada Siswa SD dan MI di Kelurahan Langgam - Sakur Sakur; Azka Fillani; Apfia Natalie Jhonatan; Nilam Sukma (Universitas Pahlawan Tuanku Tambusai, 2022)
The use of mobile phones is very helpful in human life. However, for children who are still said to be teenagers, excessive use of cellphones will have a negative impact on social life in their environment. This socialization activity aims to provide an understanding to teenagers about the negative impacts caused by excessive use of cellphones. This socialization activity was carried out in two schools in Langgam District, namely SD 001 and MI.